EMPLOYEE WORK PRODUCTIVITY AT THE CENTRAL JAVA II REGIONAL OFFICE OF THE DIRECTORATE GENERAL OF TAXES - Wintari, Wienka; Istiatin, Istiatin; Sudarwati, Sudarwati (STIE Pelita Nusantara Semarang, 2025)
This research aims to examine and analyze The influence of discipline on the work productivity of employees of the Regional Office of the Directorate General of Taxes, Central Java II, The influence of motivation on the work productivity of employees of the Regional Office of the Directorate General of Taxes, Central Java II, This research is categorized as a quantitative research type. The population and sample in this research were all employees at the Central Java II Regional Office of the Directorate General of Taxes, namely 151 people. And 50% of employees, namely 75 employees, were sampled, so this research used a saturated sampling technique. Data collection techniques use observation, documentation and questionnaire methods. The data analysis technique in this research uses multiple linear regression analysis. Based on the research results, it was concluded that Discipline had a significant/not significant effect on work productivity at the Regional Office of DJP Central Java II, Motivation had a significant effect on employee work productivity at the Regional Office of DJP Central Java II, Competence has a significant effect on the work productivity of employees at the Regional Office of DJP Central Java II, and Work culture has a significant effect on the work productivity of employees at the Regional Office of DJP Central Java II.